(1043) مدخل في اعـداد خطـط تطوير وتشغيل أسطول الصناعة السمكية في المياه البعيدة Introduction to the Preparation of Plans for the Development and Operation of the Distant-Water Fishing Fleet - أحمد, عبد الوهاب برانية (معهد التخطيط القومى, 2025)
42 ص